2022
DOI: 10.1590/1413-81232022278.04632022
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of food for away-from-home consumption in Brazil between 2002 and 2018

Abstract: The aim of the study was to assess the evolution of food acquisition for away from home consumption in Brazil from 2002 to 2018. The trend of food purchases for out-of-home consumption in Brazil was evaluated by comparing food purchase data from the Household Budget Surveys (HBS) of 2002-2003, 2008-2009, and 2017-2018. The frequency of food acquisition was estimated according to sociodemographic variables and the mean cost. In 2002-2003, the frequency of purchase of food for out-of-home consumption was 35.2% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In Chile as in other Latin American countries, eating away has been increasing in the past decades although the quality of the food purchased varies significantly depending on the socioeconomic classes. In Brazil, it has been reported that people of the highest income levels present the highest expenditure on out-of-home food ( 47 ). During the COVID-19 lockdown, there is evidence that families from higher educational levels and higher income were the ones that most frequently used digital channels to access food ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Chile as in other Latin American countries, eating away has been increasing in the past decades although the quality of the food purchased varies significantly depending on the socioeconomic classes. In Brazil, it has been reported that people of the highest income levels present the highest expenditure on out-of-home food ( 47 ). During the COVID-19 lockdown, there is evidence that families from higher educational levels and higher income were the ones that most frequently used digital channels to access food ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have examined various attributes of AFHF, such as nutrition, economy, safety, and social issues. However, environmental sustainability is still in its early stage of research and has received insufficient attention from governments [ 13 , 14 , 15 , 16 ]. Our hypothesis is that AFHF consumption increases the carbon footprint of the diet.…”
Section: Introductionmentioning
confidence: 99%